ED50 value of remifentanil in inhibiting coughing during extubation in children with snoring - Chen, Dong-Mei; Yang, Min; Ren, Xiao-Ye; Su, Shi-Peng; Li, Ling; Jia, Qi; Zhong, Hai-Yan; Yan, Jian-Ping (Frontiers in Pharmacology, 2022)
Objective: This study aimed to determine the effective dose 50% (ED50) value of remifentanil in inhibiting coughing during extubation in children with snoring. Methods: The subjects were children who scored a grade I in the American Society of Anesthesiology (ASA) metric and who were undergoing tonsillectomy (with or without adenoidectomy) under general anesthesia. Using Dixon’s up-and-down sequential method, the initial infusion rate of remifentanil was 0.06 μg/kg/min, and the difference between the infusion rates of the two adjacent groups was 0.01 μg/kg/min. If a child had no cough response during extubation, the infusion rate for the next child was reduced by 0.01 μg/kg/min. If that child had cough response, the infusion rate for the next child was increased by 0.01 μg/kg/min, and the test was terminated when seven pairs of children with positive-negative alternating results were obtained. The ED50 value and its 95% confidence interval (CI) were calculated by probit regression. The times for extubation, awakening, agitation, and respiratory complications after extubation were compared between the two groups. Results: 1) The ED50 value of a continuous infusion of remifentanil required to inhibit the cough response of children during extubation was 0.042 μg/kg/min, and the 95% confidence interval was 0.025–0.062 μg/kg/min. 2) The total dosage and infusion rate of remifentanil in the cough suppression group were higher than those in the cough group (p < 0.05), but the differences in the times for extubating and awakening between the two groups were not statistically significant (p > 0.05). 3) There was no correlation between the infusion rate of remifentanil and the time for extubating and awakening in the cough suppression group; the r values were 0.13 and 0.12, respectively, and p > 0.05. 4) The differences in postoperative respiratory complications between the two groups were not statistically significant (p > 0.05). Conclusion: The ED50 value of a continuous infusion of remifentanil required to inhibit the cough response of children during extubation after tonsillectomy (with or without adenoidectomy) was 0.042 μg/kg/min, and a low-dose infusion of remifentanil does not affect the times for awakening and extubating in children.